Parasympathetic functions in children with sensory processing disorder - Schaaf, Roseann C.; Benevides, Teal W.; Blanche, Erna; Brett-Green, Barbara A.; Burke, Janice; Cohn, Ellen; Koomar, Jane; Lane, Shelly J.; Miller, Lucy J.; May-Benson, Teresa A.; Parham, Diane; Reynolds, Stacey; et al. (Frontiers in Integrative Neuroscience, 2010)
The overall goal of this study was to determine if Parasympathetic Nervous System Activity (PsNS) is a significant biomarker of sensory processing difficulties in children. Several studies have demonstrated that PsNS activity is an important regulator of reactivity in children, and thus, it is of interest to study whether PsNS functioning affects sensory reactivity in children who have a type of condition associated with Sensory Processing Disorders (SPD) termed Sensory Modulation Dysfunction (SMD). If so, this will have important implications for understanding the mechanisms underlying sensory processing problems of children. The primary aims of this project were to: (1) evaluate PsNS activity in children with SMD compared to typically developing (TYP) children, and (2) determine if PsNS activity is a significant predictor of sensory behaviors and adaptive functions among children with SMD. As a secondary aim we examined whether subgroups of children with specific physiological and behavioral sensory reactivity profiles can be identified. Results indicate that the children with severe SMD demonstrated a trend for low baseline parasympathetic activity, compared to TYP children, suggesting this may be a biomarker for severe SMD. In addition, children with SMD demonstrated significantly poorer adaptive behavior. These results provide preliminary evidence that children who demonstrate SMD may have physiological responses that are different from children without SMD, and that these physiological and behavioral manifestations of SMD may affect a child’s ability to engage in everyday social, communication, and daily living skills.